2017
DOI: 10.1620/tjem.243.41
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-483-5p Modulates the Expression of Cartilage-Related Genes in Human Chondrocytes through Down-Regulating TGF-<i>β</i>1 Expression

Abstract: Transforming growth factor-β1 (TGF-β1) has been reported to improve chondrocytes phenotype and function. The expression levels of microRNA-483-5p (miR-483-5p), a potential regulator of TGF-β signaling pathway, were elevated in chondrocytes of patients with osteoarthritis. In this study, we aimed to explore the role of miR-483-5p for the expression of cartilage-related genes in chondrocytes. Human chondrocytes were harvested from femoral condyle and tibial plateau of different donors (n = 10) following amputati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Col2a1 (type II collagen alpha 1) and aggrecan are major cartilage extracellular matrix proteins that are essential for normal cartilage function. Runx2 (runt-related transcription factor 2) is a transcription factor involved in chondrocyte differentiation and hypertrophy, and type II collagen-degrading MMP-13 (matrix metalloproteinase-13) contributes to cartilage degradation [18]. To determine the role of MSC-Exos in chondrocytes, we detected the levels of these key cartilage genes with MSC-Exos treatment in OA mice-derived chondrocytes.…”
Section: Msc-exos Increase Col2a1 and Aggrecan Decrease Mmp-13 And Rmentioning
confidence: 99%
“…Col2a1 (type II collagen alpha 1) and aggrecan are major cartilage extracellular matrix proteins that are essential for normal cartilage function. Runx2 (runt-related transcription factor 2) is a transcription factor involved in chondrocyte differentiation and hypertrophy, and type II collagen-degrading MMP-13 (matrix metalloproteinase-13) contributes to cartilage degradation [18]. To determine the role of MSC-Exos in chondrocytes, we detected the levels of these key cartilage genes with MSC-Exos treatment in OA mice-derived chondrocytes.…”
Section: Msc-exos Increase Col2a1 and Aggrecan Decrease Mmp-13 And Rmentioning
confidence: 99%
“…Also, OA AC micropellet cultures have higher miR-483 level, compared to normal AC micropellet cultures [210]. TGF-β1 is downregulated by overexpression of miR-483 mimic in monolayer cultures from human normal knee AC, which coincides with COL2A1 and ACAN mRNA depletion and RUNX2 and MMP13 upregulation [230]. In human MSPC miR-483 directly targets SMAD4 , which suppresses chondrogenesis.…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…2015) and catabolic outcomes (Xu et al . 2017; Wang et al . 2019); hence, its observed reduction in response to abnormal load may reflect an attempt at tissue remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in miR-483 levels was observed in response to non-physiological load and is the first report of its mechano-sensitivity in articular cartilage. Its potential role in cartilage homeostasis is not well defined, with conflicting evidence suggesting anabolic (Yang et al 2015) and catabolic outcomes (Xu et al 2017;Wang et al 2019); hence, its observed reduction in response to abnormal load may reflect an attempt at tissue remodelling.…”
Section: Discussionmentioning
confidence: 99%